2014
DOI: 10.1158/0008-5472.can-13-2971
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cell Lines for Drug Discovery and Development

Abstract: Despite the millions of dollars spent on target validation and drug optimization in preclinical models, most therapies still fail in phase III clinical trials. Our current model systems, or the way we interpret data from them, clearly do not have sufficient clinical predictive power. Current opinion suggests that this is because the cell lines and xenografts that are commonly used are inadequate models that do not effectively mimic and predict human responses. This has become such a widespread belief that it a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
286
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 366 publications
(290 citation statements)
references
References 39 publications
1
286
1
2
Order By: Relevance
“…MSI was detected in 63/151 cases (42%; Supplementary Data 1). It has been previously noted that a higher than expected fraction of CRC cell lines are MSI, conceivably because MSI tumours can be more easily propagated in vitro 15 . We also observed that the rare hypermutator/ MSI-negative subgroup, identified in about 2% of CRC cases, is represented by three lines, HT115, HCC2998 and HT55 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…MSI was detected in 63/151 cases (42%; Supplementary Data 1). It has been previously noted that a higher than expected fraction of CRC cell lines are MSI, conceivably because MSI tumours can be more easily propagated in vitro 15 . We also observed that the rare hypermutator/ MSI-negative subgroup, identified in about 2% of CRC cases, is represented by three lines, HT115, HCC2998 and HT55 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-clinical cancer research frequently involves experiments using model systems such as cancer cell lines and animal models of disease. Cancer cell lines are accessible, inexpensive and, in some cases, represent adequate disease models (Wilding and Bodmer 2014). Concerns over the impacts of cell line cross-contamination and mis-identification are now being addressed through better cell culture practices (Geraghty et al 2014) and journal-imposed requirements for researchers to authenticate cell lines using short tandem repeat (STR) profiling (Lichter et al 2010).…”
Section: The Changing Landscape Of Biospecimen Use In Cancer Researchmentioning
confidence: 99%
“…Concerns over the impacts of cell line cross-contamination and mis-identification are now being addressed through better cell culture practices (Geraghty et al 2014) and journal-imposed requirements for researchers to authenticate cell lines using short tandem repeat (STR) profiling (Lichter et al 2010). However, other limitations, such as those imposed by routine cell culture systems, the consequences of long-term passaging, including loss of tumour heterogeneity, and genetic drift from genomic instability, result in cell lines incompletely representing the original tumour state within the host (LaBaer 2012;Wilding and Bodmer 2014). The growth of cancer cell lines as xenograft models provides a three-dimensional tissue environment (Wilding and Bodmer 2014), but not always one that is orthotopic (Saletta et al 2014).…”
Section: The Changing Landscape Of Biospecimen Use In Cancer Researchmentioning
confidence: 99%
See 2 more Smart Citations